"Global Revolution of Values" in the Public Service - A. Prokhorov; N. Kadyrov (Vestnik MGIMO-Universiteta)
Book review: Sullivan H., Dickinson H., Henderson H. (eds). 2021. The Palgrave Handbook of the Public Servant. Palgrave Macmillan, Cham. 1737 р. https://doi.org/10.1007/978-3-030- 29980-4